Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1370988737 species occurrences available in GBIF matching the query: { "and" : [ "OccurrenceStatus is Present", "Year 1976-2020" ] } The dataset includes 1370988737 records from 25630 constituent datasets: 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 3876 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 19 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 39 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5916 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 435 records from Nannofossil abundance of Hole 66-490. 165 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 117 records from Fossil Specimens of Komatsu City Museum. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 974190 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 411640 records from DATAVES. 296 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 5 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1251 records from Nannofossil abundance of Hole 82-558A. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3320 records from BioGIS - Mammals - SPNI. 7 records from Planktic foraminifera abundance of Hole 53-418B. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1808 records from Berea College, Ralph L. Thompson Herbarium. 13 records from Diatom abundance of Hole 60-460. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 424 records from Distribution of nanoplankton at trap WR2. 234 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 33 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 84 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 154 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 78 records from Données de la naturaliste Anna Even. 3004 records from MEXU/Flora de Oaxaca. 22996 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 5657 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 903 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 290 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 3217 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 95 records from Kystfuruskoger i Tysnes og Fusa. 109 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 91 records from Diatom abundance of Hole 95-613. 1477 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 61 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2851 records from Données naturalistes d'Alain BERLY. 10864 records from Herps Specimens. 27826 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 2 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 12685 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 195328 records from Données de la flore d’Alsace (SBA). 2123737 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 5 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 179 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 173 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 24880 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1502 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 264 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 1 records from Données naturalistes d'Olivier DELZONS. 22882 records from Naturalis Biodiversity Center (NL) - Diptera. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 14 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 91701 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2718 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6642 records from Distribution of foraminifera of sediment core GIK23258-2. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1762 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 997238 records from Flore Franco-Belge. 57624 records from EAC - Herbário Prisco Bezerra. 2392 records from Elaboration de table de tarif de cubage multispécifique (I). 2700 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 97 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 7 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 232 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 35 records from UWYMV Herpetology Collection (Arctos). 7 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 1902 records from Midden-Limburg Fish Ponds Survey. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 61037 records from Herbarium Senckenbergianum (FR) - Fungi. 1836 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 179 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 7 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 895 records from Geometridae de France métropolitaine. 126 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 203 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 2001 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 12 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 7566 records from Inventario de Hymenóptera; parasítica en México. 407 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 740 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 22 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 144647 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 88 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from Données naturalistes de LE GLOANEC Vincent. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 370 records from Size of planktic foraminifera at CTD station PS55/051. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 247 records from Whale catches in the Southern Ocean. 401 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 16 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 55 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 26389 records from Protist Diversity in the East China Sea. 120 records from Données espèces - Expertise IPE 79. 1642404 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 275 records from South American Antarctic Marine Biodiversity Literature. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1001 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 382 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 6191 records from marine sediment metagenome Metagenome. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 608 records from Range table from benthic foraminifers in ODP Hole 146-889A. 98 records from Warnowtal (Rostock). 1956 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 137 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 37 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 159 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 2747 records from Compost microbe establishment and growth in agricultural soils. 202114 records from National Benthic Inventory. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 14 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2906 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 12 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 1746 records from Bryophyte specimens of The Nagoya University Museum. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 24447 records from University of Guam Insect Collection. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 26 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 4 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 150166 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 801 records from UWIZM Molluscs. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 32 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 5025 records from MCP-Aves - Coleção de Aves. 181825 records from Carnet B Lorraine. 26 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 674 records from Bird specimens of Saitama Museum of Natural History. 98 records from orthopteracollections-nhmj-ioj. 1 records from Carnivores of Syria. 2 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 5 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 11115 records from Collections of Bioclass, school #179, Moscow. 346977 records from Seasearch Marine Surveys in England. 38 records from Planktic foraminifera abundance of Hole 84-566C. 1 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 10 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 18 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 8 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 10 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 240451 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 46 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 6 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 269 records from Range table from benthic foraminifers in ODP Hole 161-974B. 3508 records from Collection Trichoptera - SMF. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 12 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 34724 records from Arizona State University Hasbrouck Insect Collection. 1 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 1 records from Collection Strepsiptera SMF. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 187 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3353 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 976 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 44 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 3777 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1714 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 18 records from Naturtag. 11495 records from Herbier Louis-Marie (QFA) - Collection de lichens. 10 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 6 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 432483 records from Plant. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 76 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 50 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 8 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 5 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 444 records from Colecção Entomológica IIA. 16746 records from MZFC/Coleccion de Aves. 9579 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 2645 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 29 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1264 records from Grand Voyeux - Suivis scientifiques. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 56 records from UWIZM Cnidarians. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 147 records from Données de la naturaliste Laurence Beauchamp. 23 records from Collections ichtyologiques et herpétologiques (BOUM). 42 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 12907 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 146463 records from Tasmanian Museum and Art Gallery provider for OZCAM. 96 records from TTRS Mammals. 20 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 8 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 20 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 5 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 330 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6164 records from NE Scotland fish records 1800-2010. 1233 records from Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 45 records from Brown bear monitoring data from Deosai National Park. 369 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 260 records from bmhs_weatherheadshell_collection. 96409 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 57919 records from Fichier communal des ongulés. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 308 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 11 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 39 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 6 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 26 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 2 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 61 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 604 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 222 records from Land and freshwater molluscs of Northern Spain. 1 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 3753 records from Données naturalistes de Charlotte PICARD. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 5 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 21240 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 111 records from Birdrace-Uhulogen-Lippe. 15 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5060 records from La familia Asclepiadaceae en México. 2195 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 8 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 106468 records from ALCB - Herbário Alexandre Leal Costa. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 114 records from BIRDRACE LiLaLau. 370 records from Otter survey of Ireland 2004 & 2005. 107646 records from Fish specimens of Kagoshima University Museum. 1042 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 5645 records from UTEP Invertebrates (Arctos). 413 records from Diptera Collection of Museum and Institute of Zoology PAS. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 21 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 17 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 39 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 108 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 878 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 871 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 361 records from Données de VINCENT Alexis (SAPROX). 26 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 243 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 34 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 30 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 6 records from Foraminifera abundance of Hole 58-442. 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 10 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 28 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 13 records from Coleção de Coleoptera da Universidade de Brasília. 64370 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 4604 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 16821 records from Données Entomologiques A. HORELLOU 1988-2018. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 558 records from Foraminifera abundance of Hole 74-526A. 70 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 16 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 10727 records from WOLL AVH data. 2 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 85 records from Ostracoda abundance of Hole 48-403. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 43 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 93 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 2 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 2497 records from Données des collections d'algues du MNHN. 11423 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 223 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 1 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 422150 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 313 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 15 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'intérêt communautaire. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 5 records from Loricifera - SMF. 3 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 267 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 475643 records from KTP Ring Data. 41 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 584 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 10 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 504 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 1 records from Brown University Herbarium. 90 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19339 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 51 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 36 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 7 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 3 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de données Natura 2000. 1170 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 21 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 20 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 7 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1012 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 7 records from Amphibian Specimens of the Yamagata Prefectural Museum. 27 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3250 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 21 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 59 records from Schulgelände SGD/Viersen. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 1263 records from Flora genérica de las gramíneas del estado de Tlaxcala. 59 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 1049 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 4 records from Natural History Museum Maastricht (NL) - Herbarium. 5427 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 1300 records from Crustacean specimens of Bihoro Museum. 361 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 58 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 3 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 65 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 4 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 12 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 61 records from Shrews of Poland. 81 records from DMNS Egg Collection (Arctos). 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 147 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 180153 records from Marine benthic dataset (version 1) commissioned by UKOOA. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 29876 records from European Moth Nights. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 260 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6779 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 245 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1699 records from BioGIS - Bryophytes - HUJ collections. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59995 records from Données naturalistes de Monsieur François FOURNIER. 743 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 54138 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 270 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 2208 records from marine sediment metagenome Raw sequence reads. 774 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 572 records from UWYMV Bird Collection (Arctos). 752 records from Données naturalistes de Monsieur JOURDE Rémi. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 7 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 1247360 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 3 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 42 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 12 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 120 records from BIRDRACE The early birds. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2210 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 356 records from Morphologische Daten von Puffinus creatopus. 22862 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 21849 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 6979 records from Upper Silesian Museum, Bird Observations. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 243 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 78 records from Herbarium BSG Hepaticopsida. 18 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 115 records from SEWBReC Springtails and allies (South East Wales). 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 74227 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 60 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 80 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1533 records from Leif Richardson Vermont Bee Specimens. 10 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 16 records from Insect Collections of Okomu National Park- Nigeria. 265643 records from ARABEL - Arachnologia Belgica. 48144 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1886 records from Collection Crustacea - ZMB. 645 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 25 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 458 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 6 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 103 records from Coccoliths in sediment core GIK23065-3. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 49 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 15 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 231 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 7 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 973 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6108 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 23 records from Analyses of the recent components of sediment core PS1219-1. 40664 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 347 records from HBRG Invasive Non-native Plants Dataset. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 63370 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 44 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 7689 records from Birds Specimens. 94 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 13304 records from DMNS Mammal Collection (Arctos). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 64 records from Bats of northeastern Vietnam. 1052 records from IBF Monitoring of Fungi. 20 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 6 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2380 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 23 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 64 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 202 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 240 records from Knechtweide (Kohlfurth). 3919 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 1397 records from MCP-Mamiferos - Coleção de Mamíferos. 19 records from Benthic macrofauna abundance of sediment core 12930-073. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 39 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 80 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 342 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 5496 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Nivelle (France). 132 records from Colección Ficológica del Herbario Criptogámico de la FML. 62 records from Données naturalistes de BONCHE Jérôme. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 56936 records from natagora-earlybirds. 9097 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 20 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 13 records from Reptiles Specimens of Akita Prefectural Museum. 167 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 8 records from Données bibliographiques ASFRA. 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 24 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 768 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Nymphalidae). 6262 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 4585 records from Marine bacteria Targeted Locus (Loci). 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 38 records from Atlantic Forestry Centre Insect Reference Collection. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 93 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1469 records from Marine eukaryotes Targeted loci environmental. 9 records from The Amphibians of the Mitaraka massif, French Guiana. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1583 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 4 records from Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China. 15067 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 20713 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1199 records from Oxygen minimal zone Targeted loci environmental. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 4 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 7387 records from Ibaraki Nature Museum, Fungi collection. 190 records from Relative abundance of ostracods in sediment core Sv09. 923 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 384 records from Saltern microbial community diversity. 93599 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 24 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 4142 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 312 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 33093 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 11 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 9 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 738 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1145 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 11 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 118 records from Radiolaria assemblage in sediment core GIK23400-3. 877 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 68 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 22109 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5649 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 10 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 2 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 34 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 10 records from Colección de helechos de la FML. 3 records from Zoology in the Middle East. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 51587 records from Données de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 4147 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 164 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 9 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 156 records from Phenological Center - Birds (Murmansk). 9 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 95 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 4337 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5270 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 199 records from Echinoderms from the Seaflower Biosphere Reserve. 300 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 2 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 868 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 230 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 23 records from Analyses of the recent components of sediment core PS1011-1. 57 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 50 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 19 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 3 records from A Catalogue and Historical Study of the Odonata of Ecuador. 557 records from Corn bunting breeding distribution in Scotland. 1 records from -- First- - description -- of- - the- - male- - of- - Dendrothrips karnyi (Thysanoptera, -- Thripidae) - from- - Iran. 3186 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 15 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 40793 records from Banded Iron Formation and Greenstone survey data. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 2 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 39 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 5 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1900 records from Fungi Collection. 87 records from Données espèces - Expertise IPE 70. 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 118 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 18024 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 52292 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 23 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 67 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 1 records from A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) on palms in Costa Rica and a new country record for Haplaxius skarphion. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 4923 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 60 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1 records from A new tyrannosaurine (Theropoda: Tyrannosauridae) from the Campanian Foremost Formation of Alberta, Canada, provides insight into the evolution and biogeography of tyrannosaurids. 24 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 148 records from Abundance of birds in the Lena Delta Region. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 95 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 381 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 2212 records from Colección Ornitológica de la Universidad del Valle. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 29 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 142 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 491 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 181 records from Total foraminifera counts from multinet M31/3_MSN915. 765653 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 946 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 35 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 12 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 12487 records from Florida Keys Reef Visual Census 1996. 2 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 172723 records from Wild bees of Belgium. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 3170 records from Royal British Columbia Museum Entomology Collection. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 106 records from Dinoflagellate abundance of Hole 81-552. 24 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 11 records from Eight new Lepadellidae (Rotifera, Monogononta) from the Congo bring to level endemism in Africa’s rotifers. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 144 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8409 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3001 records from Colección Entomológica CDMB. 1046 records from NZCS Invertebrates New Collection After 1987. 10198 records from Lepidoptera (Specimens NRM). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 149 records from Las comunidades de myxomicetes de selva baja caducifolia. 10230 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 140 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 21108 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 25 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4607 records from Données de type contact en Guadeloupe. 588 records from Canadian Museum of Nature Palynology Collection. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 136 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 55 records from Galls on Beech Trees in Hainich, 2008. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 2290 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 1741 records from Occurrence database of native plants and animals of south-central Chile. 1 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 259 records from Natura 2000 Parc naturel régional de Lorraine. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 213 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 1562 records from Helmintos parásitos de peces del sureste de México. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 115 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 8 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 356 records from Données naturalistes de Hubert GUIMIER. 1606 records from Données de la collection Rousset -1947-2013. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 136 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 12094 records from Amino acid addition experiment Metagenome. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 45762 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 9 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 17 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1968 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 1022 records from Insectes Hyménoptères Scollidés de France. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 565 records from IOW Natural History & Archaeological Society Marine Records. 15 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6190 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 16 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 152 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 35 records from Données de NICOLAS Vincent (SAPROX). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 2572 records from seawater metagenome Metagenome. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3806 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 5372 records from Fish specimens of Toyama Science Museum. 132 records from Range table from ostracoda in ODP Hole 143-866B. 5983 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 60538 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 10 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1953 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 15638 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 10 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 10965 records from Lepidoptera specimen database of Japan. 292608 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 374 records from Planktic foraminifera abundance of Hole 68-503B. 130 records from BIRDRACE - The famous Grouse feat. The James. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 13 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 5429 records from Insectes Hétéroptères Mirides de France. 8 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 701 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 749 records from Pollen analysis of sediment core GeoB6518-1. 1070 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 23 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 29 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 144 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle RNC:102. 7 records from Grundwasserlebensraum im Englischen Garten (München). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 12 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 4289 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 678 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 1845 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 20763 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 2165 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 347 records from Bird specimens of Bihoro Museum. 2 records from Wie viel Natur gibt es im Park?. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 866 records from Zootaxa. 1 records from A review of South Korean Alloplasta Förster (Hymenoptera: Ichneumonidae: Banchinae) with description of a new species. 8154 records from NBMB Herps. 386 records from Foraminifera distribution of sediment core KS310. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 11079 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 50 records from Données d'observation de phanérogames marines en Martinique. 191 records from Nannofossil abundance of Hole 67-499. 374 records from Coastal and Marine Species Database. 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 3 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 224 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 203 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 204 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1689 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 230 records from UTEP Fish (Arctos). 1 records from Two new species of Leptarma (Decapoda, Brachyura, Sesarmidae) from the Western Indian Ocean with notes on their phylogeny. 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Rediscovering Anhanga: redescription and considerations on its taxonomic placement (Hemiptera: Heteroptera: Pentatomidae). 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 24 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 2500 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 610 records from BID-Malawi-Geometridae-Biodiversity-Data. 129 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 2634 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 40 records from A revision of the African wolf spider genus Amblyothele Simon. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 2400 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 2 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 72773 records from NINA Vanndata fisk. 21 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 510 records from Inventaires des cygnes du département de l'Eure. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 53062 records from British Antarctic Survey Argos satellite tracking data. 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 114 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 2 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 1 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 584 records from Données du naturaliste Christian Desmier. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 191 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 8003 records from Données naturalistes de Franck NOEL. 365 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 1403 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 117 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 176 records from Planktic foraminifera abundance of Hole 94-610B. 406 records from Global database of alien macrofungi. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 2118 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 70 records from Arizona State University Lois B. O'Brien Collection. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 7 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 7326 records from Ravensthorpe Range survey data. 24 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 25783 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 5 records from Schulinnenhöfe (Gelsenkirchen). 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1462 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 346 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 647919 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 7 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 115 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 1169 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 22 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 546 records from Rare plants database extract from Scottish Natural Heritage. 14 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 23927 records from Formidabel; Belgian Ants Database. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 145 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 511 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 108 records from Сypripedium guttatum Sw. in the Komi republic. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 32 records from Nanoplankton abundance at station GeoB2012-5. 834 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7490 records from Yoann_BLANCHON_2017_12_18. 2 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 2 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 60 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 3 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 10974 records from Wikiplantbase #Sicilia. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 496 records from Phenological Center - Birds (Laplandskiy). 681 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 527 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 680756 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 163 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 15 records from CNIN/Tipos Homoptera. 29016 records from Marine Biological Sample Database, JAMSTEC. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 303 records from Otter (Lutra lutra), Outer Hebrides. 416 records from The Living Murray Fish data. 4429 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 25974 records from Long-term Bird Census in Cigu 2004-2017. 5 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 240 records from BARTH-Environnement_2017_12_18. 1128 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 325 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 162 records from Total foraminifera counts of multinet M21/2_MSN658. 25 records from Microzooplankton abundance and biomass at station TT043_11-1. 2332 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 556 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 15 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 61547 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 10 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 132 records from Total foraminifera counts of multinet POS247/2_MSN1377. 2394 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 4 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 48 records from FBIP: Establishment of a fully data-based and barcoded collection of mushroom pathogens for South Africa. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 87 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 2041 records from marine metagenome Targeted Locus (Loci). 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 4181 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 26573 records from Plan de vertebrados de la Patagonia. 1 records from Notes on the genus Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from India with description of a new species. 8 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 2695 records from AlgaTerra. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 148 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 13000 records from LPO_PACA_2017_12_18. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 34 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 5265 records from HSU Vertebrate Museum Mammals Collection. 17 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 8 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 348 records from Foraminifera abundance of Hole 57-440B. 128 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 6664 records from Coral or reef-seawater associated bacteria Targeted Locus (Loci). 6437 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 16260 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 2 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 24146 records from UTEP Insects (Arctos). 7152 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 14 records from A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 4 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Données naturalistes de DURON Cyril. 8936 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41037 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 13070 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 39 records from Inventaire Faune. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 49 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 72 records from Registros de la araña del banano (Phoneutria boliviensis) en los departamentos de Antioquia, Huila y Tolima. 444 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 6 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 21 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 170 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 429 records from NHMO DNA Bank Other groups collection. 69 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 22 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 3 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 5 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 75 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 22379 records from University of Michigan Museum of Zoology, Division of Birds. 2 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 811 records from Données naturalistes de AUNEAU Florent. 2203 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 640 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 28 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 24 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 870757 records from Fungal Records Database of Britain and Ireland. 131 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 45437 records from La familia Asteraceae en México. Fase VI. 620 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 128 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 202 records from Mycological collection of the National Museum. 20 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 6808 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 84 records from Total foraminifera counts from M35/1_MSN1051. 1514 records from Gemeinde Sursee. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 3 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 566 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 214 records from Nannofossil abundance of Hole 67-496. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 508 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1018 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 1 records from On Megalepthyphantes lydiae Wunderlich, 1994 (Araneae: Linyphiidae). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 24 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 323 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 3006 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 285123 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 8 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 11 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 36879 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 1288356 records from Biodiversitätsdatenbank des Landes Salzburg. 9023 records from NCSM Mammals Collection. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17 records from Nannofossil abundance of Hole 52-418. 76 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 103 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 218 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 6 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 3036 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 8 records from The cavernicolous Oniscidea (Crustacea: Isopoda) of Portugal. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 230 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 2336 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 1 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 2167 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 5 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 173 records from pbzt_insect_biodiversity. 82 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 19644 records from Insect specimens of Himeji City Science Museum. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 3477 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 3 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 245 records from NZCS Upper Tapanahony Expedition 1991. 174 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Description of the female of Chelis ferghana Dubatolov, 1988, an endemic moth species of the Tien Shan Range in Central Asia (Lepidoptera: Erebidae Arctiinae). 153 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 5679 records from Fish specimens of Natural History Museum, Kishiwada City. 347 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 6107 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 5 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 60 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 29 records from Naturerfahrung. 634 records from ISM Herpetology Collection. 205 records from Total foraminifera counts from M35/1_MSN1047. 953 records from Données naturalistes de Damien Combrisson. 4142 records from Range table from benthic foraminifers in ODP Hole 159-962D. 6652 records from Inventory of plant species through Benin (West Africa). 6 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 150 records from Total foraminifera counts of multinet M12/3_MSN535. 553 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 896 records from Data on agroforestry plant species of Benin. 29 records from Données malacologiques du site Natura 2000 de Cessière-Montbavin. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 3460 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 8 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 16 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 4 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 27 records from Benthic macrofauna abundance of sediment core 13078-013. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 5 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 4 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 25 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 189 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 661 records from Données espèces Expertise IQE 311. 4 records from Groundwater amphipods (Crustacea, Malacostraca) of India, with description of three new cavernicolous species. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 155 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 28202 records from India Biodiversity Portal publication grade dataset. 224 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 42 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 858 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 983 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Lycaenidae). 1 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 205 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 2114 records from All herbarium specimens of grasses held at TAN herbarium. 4 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 6 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 704 records from Pollen counts of sediment core GeoB9503-5. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 18 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 136 records from Total foraminifera counts from multinet M32/3_MSN956. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 6164 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 102 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 32 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 3 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 2893 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 3 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 19 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3304 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 331 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 197 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 53 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 3 records from A new species of the genus Zographetus Watson, 1893 from China (Lepidoptera: Hesperiidae). 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 1 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 2456 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 32 records from Abundance of coccosphere-units of sediment core GIK23071-3. 3 records from Description of Moca austrasinensis sp. nov., with the first record of Imma lathidora Meyrick, 1914 from mainland China (Lepidoptera, Immidae). 272620 records from Parc_National_de_Port_Cros_2017_12_18. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 869 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 35965 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 11 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 30 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 24 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 10793 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 3893 records from Colección Carcinológica de Yucatán. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 113 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 14 records from Benthic foraminifera abundance of Hole 96-620. 4358 records from FrogWatch SA. 105 records from Nanoplankton abundance at station GeoB2006-4. 33 records from Données naturalistes de Françoise SERRE-COLLET. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2331 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 3 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 131 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Pieridae). 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 4 records from Dinoflagellate abundance of Hole 71-513A. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 234 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 243 records from Thistles species and abundance. 222 records from Total foraminifera counts of multinet SO118_MSN1253. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1613 records from The Vascular Plants Collection of the University of Goettingen. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2076 records from Flora vascular acuática de la cuenca del Río Tamesí. 13 records from A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil. 1293 records from Foraminifera abundance of Hole 45-396. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 4 records from A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 8 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 33 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 4584 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 725 records from Données naturalistes de Stéphane ORIO. 260 records from Miljodir_naturtypekartlegging_2017. 1 records from Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea). 320 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3868 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 406 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 21 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 16 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 20546 records from CPAP - Herbário CPAP. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 166 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 28 records from Harpactus Shuckard. 2827 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 2314 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from First record of Caliscelis (Caliscelis) bonellii (L, 1807) (Hemiptera: Fulgoromorpha: Caliscelidae) from Turkey, with redescription of the species. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 91 records from Données de la naturaliste Marie Melun. 51 records from Données du naturaliste MARCHAL Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 1419 records from Diversity of algae in wetlands. 41 records from List of Snail species in Vava'u. 3989 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 346 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 3 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 4 records from Open-holed trapdoor spiders of the genus Teyl (Mygalomorphae: Nemesiidae Anamini) from Western Australia’s Pilbara bioregion: a new species and expanded phylogenetic assessment. 330 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 129 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 3050 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 11193 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 9 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 3 records from Two new species of the Simulium (Simulium) tuberosum species-group (Diptera: Simuliidae) from Palawan, the Philippines. 1752 records from Phytoplankton abundance in surface water during cruise CD61. 20 records from Discovery of a new species of Lacon Laporte (Coleoptera: Elateridae: Agrypninae) endemic to Cyprus, with a modified tarsal morphology. 29 records from Total foraminifera counts of trap L3_92_45. 5083 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 88 records from "Schlechteberg" Ebersbach/Sa.. 17 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 24 records from 2019_nsmk_smpl_ms_20200603. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 1 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 4686 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 89 records from Planktic foraminifera abundance of Hole 63-470A. 470 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 60 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 2 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 5 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 10 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 15 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 25 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 694 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 189 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10016 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 35 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 617 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16505 records from Database for alien invasive plants occurrences in Germany. 37 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 884 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8951 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 15 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 50 records from New species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) of the families Philosciidae and Scleropactidae from Brazilian caves. 154 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 17044 records from OUPR - Herbário "Professor José Badini". 2017 records from Flore des reliques forestières de la commune de Dangbo. 15 records from Nannofossil abundance of Hole 58-442B. 1 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 4 records from Gynacantha vargasi (Odonata: Anisoptera: Aeshnidae) sp. nov. from Costa Rica. 63 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 316 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 2 records from A new species of the genus Foenatopus Smith (Hymenoptera: Stephanoidea Stephanidae) from India. 11830 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 3 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 74 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 106 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 533 records from California State University, Long Beach Mammals. 198 records from Royal Saskatchewan Museum - Ichthyology Collection. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 981 records from Monitoreo de la ocupación del Oso Andino Tremarctos ornatus en el Parque Nacional Natural Chingaza 2010. 4265 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 45 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 74 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 61 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 2461 records from Inventaire des Mollusques Sphaeriidae de France. 14821 records from données aranéologiques de CORNIC Jean-François. 23 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 347 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 3687 records from Clare Biological Records Centre Dataset 2004-2007. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 7 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 2115 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 15 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 16 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 122 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 4701 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 696 records from Biological Collection, National Institute of Oceanography, Goa, India. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 142 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 603 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 12699 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 200 records from Insect specimens of Natural History Museum, Kishiwada City. 120 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 18 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 22 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 75 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 94 records from Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Planktic foraminifera abundance of Hole 54-428. 517 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 48 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 6776 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 21 records from Benthic macrofauna abundance of sediment core 13200-045. 1 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 2283 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 271 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 3394 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 136 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 10024 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano (Larvas de peces). 11616 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 244 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1313 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 421 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 79 records from Plant specimens of the Museum of Yamagata University. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 14203 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 150 records from Registros de almeja (Polymesoda arctata) en la Ciénaga de pajarales. 18 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Ácaros acuáticos). 110 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 119769 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 98396 records from Hymenoptera specimen database of Kyushu University. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 1 records from Thismia nigricoronata, a new species of Burmanniaceae (Thismieae, Dioscoreales) from Vang Vieng, Vientiane Province, Laos, and a key to subgeneric classification. 162917 records from Finnish Floristic Database (Literature Sources). 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 30 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 56626 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 3 records from Two new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Thailand. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 32103 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 20217087 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 161 records from Swedish Malaise Trap Project (SMTP) - Rogadinae. 1045 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 1 records from Microplankton counts and carbon biomass at station TT011_12-CTD150. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 2 records from A new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from South India. 125453 records from CNS AVH data. 858 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 3178 records from Newfoundland sediment pyrosequencing. 1 records from Diplecogaster tonstricula, a new species of cleaning clingfish (Teleostei: Gobiesocidae) from the Canary Islands and Senegal, eastern Atlantic Ocean, with a review of the Diplecogaster-ctenocrypta species-group. 2 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 736 records from The Azooxanthellate Scleractinia (Coelenterata: Anthozoa) of Australia. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 5 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 9083 records from Inventaire de la flore des Pyrénées-Atlantiques 2007-2008 - Littoral. 1482 records from Nannofossil abundance of Hole 94-607. 2146 records from Thrips (Thysanoptera) in Norway. 70 records from Levantamento de Mamíferos do Parque Nacional da Quiçama - INBAC/RWCP - 2017. 227 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 4065 records from Microbial community in permeable intertidal sediment. 51736 records from AUM Fish Collection. 69 records from Entdeckertour am Muldestausee 1/05. 66443 records from University of Colorado Museum of Natural History Herbarium Vascular Plant Collection. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 61 records from Mammalian Specimens of the Yamagata Prefectural Museum. 103 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 4 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 53 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 5 records from New species of Rhizomyces (Ascomycota, Laboulbeniales) parasitic on African stalk-eyed flies (Diptera, Diopsidae). 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 15 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 256 records from Ghent University - Zoology Museum - Vertebrate collection. 20818 records from ARKO kulturmarkseng. 108 records from BIRDRACE Diesmal sehen wir mehr. 527 records from Arthropod specimens of Natural History Museum, Kishiwada City. 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 1 records from Contributions to the taxonomy, identification, and biogeography of Casinaria Holmgren and Venturia Schrottky (Hymenoptera: Ichneumonidae: Campopleginae). 21 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 51 records from Données du/de la naturaliste Allayaud Manon provenant de la base de donnée du SINP Île-de-France CETTIA. 1764 records from Arachnida of Costa Rica (INBio). 202 records from Total foraminifera counts of multinet M21/3_MSN663. 675 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 2498 records from Ross A. Layberry, Collection. 576 records from Collembola of Kolguev, Malozemelskaya tundra and Delta Pechora. 2 records from Evaluating the generic definition of Lithopolia Yoshimoto, 1993 with a description of one new species of Taiwan (Lepidoptera, Noctuidae, Noctuinae, Orthosiini). 3 records from Notomicrus petrareptans sp. n., a new seep-dwelling species of Noteridae from Suriname (Coleoptera: Adephaga). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 1308 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 37 records from Taxonomic review of Ablabesmyia Johannsen (Diptera: Chironomidae: Tanypodinae) from Oriental China, with descriptions of six new species. 3 records from Rediscovery of Cnemaspis nilagirica Manamendra-Arachchi, Batuwita and Pethiyagoda, 2007 (Squamata: Gekkonidae) from Kerala, India with notes on morphology and distribution. 11277329 records from Finnish Bird Ringing and Recovery Database. 119 records from Microfossil abundance of Hole 50-416A. 66 records from Winter Foraging Locations Of Southern Ocean Predators - sub-Antarctic islands 2008/09. 56426 records from New Zealand Fungal and Plant Disease Collection (PDD). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) from Ninh Binh Province, Vietnam. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 13 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 5 records from A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Cerrado-Amazonian forest transition zone, Brazil. 219 records from Umgebung der Grundschule Oderberg. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas (Plantas). 4313 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 3 records from Establishment of the new genus Parvuspina for an undescribed Lithosiini species of Asura / Miltochrista generic complex (Lepidoptera: Erebidae: Arctiinae). 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 4 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 3 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 427 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 855 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 770 records from Nannofossil abundance of Hole 64-476. 7 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 16597 records from Colección general del plantas vasculares del Herbario JBB. 93058 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 159590 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 37 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 194 records from Cowan Tetrapod Collection - Herpetology. 173 records from Total foraminifera counts from multinet M31/3_MSN898. 9 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 232 records from Phytoplankton abundance at station CD46_0705C#4. 10 records from Upper Silesian Museum, Bird Collection. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 29 records from Hemmerder Schelk (Unna). 5 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 30998 records from Elephant Seal Sightings, Macquarie Island. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 116 records from CHAS Botany Collection (Arctos). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 1814 records from UKSBA Cyprus - Habitat Samples, 2019. 414675 records from Herbarium of Taiwan Forestry Research Institute. 24 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 210 records from Herbario de la Universidad de Sevilla, SEV-Historico. 11 records from ALP-PAGES_2017_12_18. 23 records from Ackerrain Plönhagen. 6562 records from Colección Herpetológica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 207 records from Malawi-Histeridae-Biodiversity-Data. 1994 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia) (Tejido). 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 9 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 22 records from Bachabschnitt der Nette (Osnabrück). 20224 records from Phenology and biological traits of migrating eels sampled by trapping in the survey in the Bresle river (France). 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 371 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 3 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 34 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 22140 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 132 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 11664 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 3438 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 178607 records from CAS Botany (BOT). 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 11715 records from CCA_pathobiome. 2225 records from Données naturalistes d'Anaïs MAS. 2430 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 8 records from Three New Species Of Aegla (Anomura) Freshwater Crabs From The Upper Uruguay River Hydrographic Basin In Brazil. 1 records from A new genus of Oxypodina from Kyrgyzstan (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini). 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 1534 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 6 records from Abundance of benthos infauna at station GIK23065-1. 12 records from List of Lizard species recorded in Vava'u during BioRAP. 1205 records from uncultured eukaryote Raw sequence reads. 16458 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 214 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 4 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 9 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 2750676 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 830 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 146 records from Bishop's University Insect Collection (BUIC). 194 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 598 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 5346 records from Sediment metagenome. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1 records from A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region. 5 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 28 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 2133 records from UMNH Reptiles and Amphibians Collection (Arctos). 17186 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 3 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 1051 records from CNAN/Scorpiones. 72 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 1 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 1 records from A new species of genus Nippononebria Uéno (Coleoptera, Carabidae, Nebriini) from Changbai Mountain, Jilin Province, China, the first species of the genus confirmed from the Asian mainland. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 51391 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 492 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 114 records from BIRDRACE Di-Bi-Di-Birder. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 4 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 63 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 105 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 3 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 2744 records from HerbarioHerrerense. 2 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 957 records from Colecção Entomológica do Museu de História Natural de Maputo. 3 records from Revisiting Calohypsibiidae and Microhypsibiidae: Fractonotus Pilato, 1998 and its phylogenetic position within Isohypsibiidae (Eutardigrada: Parachela). 5011 records from Inventario arbóreo del Jardín Botánico Universitario del campus Meléndez de la Universidad del Valle, Santiago de Cali.. 11 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 241 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 86 records from Oiseaux(Faune des mangroves et des zones humides du sud Togo). 722 records from Heritage Trees of Ireland. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 443 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 11738 records from Variation in freshwater stream sediment community 16S rRNA profiles along an urbanization gradient. 1 records from Confirmation of Trachischium guentheri (Serpentes: Colubridae) from Tibet, China, with description of Tibetan T. monticola. 73 records from VFD-HH/SH: Pferdweide Lammert. 2140 records from Données espèces - Expertise IQE 92. 2148 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 138 records from Elaboración de la base de datos de la colección de cepas de bacterias fitopatógenas de la Dirección General de Sanidad Vegetal. 8 records from RISC Non-Native Species Records for Zebra Mussel. 209 records from Nannofossil abundance of Hole 55-433. 11 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 39 records from Planktic foraminifera abundance of Hole 73-522A. 844 records from (
Keywords: GBIF; biodiversity; species occurrences